Sustainable Tourism: Ethical Alternative or Marketing Ploy? - Lansing, Paul (Journal of business ethics, 2006)
While tourism is often seen as a welcome source of economic development, conventional mass tourism is associated with numerous negative effects, such as the destruction of ecological systems and loss of cultural heritage. In response to these concerns, a term that has surfaced recently is, sustainable tourism. This article attempts to define sustainable tourism and asks the question of whether this new term is an acceptable criteria or is merely a marketing ploy to attract the morally conscious tourist.